Parental coping and distress with regard to health-related quality of life in adolescent survivors of childhood cancer - Blasco, Tomás; Castellano, Carmina; Sánchez de Toledo, José; Gros, Lluís; Capdevila, Lluís; Pérez-Campdepadrós, Marta (Psicooncología, 2010)
Purpose: To explore whether Health-Related Quality of Life (HRQoL) in a sample of adolescent survivors of childhood cancer is related to parental coping and/or parental emotional distress. Methods: Sixty-two participants (31 adolescent survivors of childhood cancer and 31 parents) completed several questionnaires in a cross-sectional study. HRQoL was assessed using the SF-12v2 questionnaire. Parental coping styles were assessed using the COPE (dispositional version); and their emotional distress with regard to the oncological experience was assessed by means of two 5-point numeric scales. Medical and demographical data were obtained from medical records. Results: The parental coping style of engagement explained 25% of the variance in mental component dimension of HRQoL of adolescent survivors of childhood cancer (ß = -,500; p = ,004). Conclusions: HRQoL of adolescent survivors of childhood cancer does not depend only of their own determinants. The family context will play a major role in their adaptation. Therefore it is necessary to take care of the needs of both patients and their parents, encouraging a greater adjustment to the remission phase, helping them to reduce the emotional distress after the end of treatment, and somehow, fostering a better and faster adjustment to the situation of the whole family.
Keywords: Parents; Adolescent survivors of childhood cancer; Coping styles; Emotional distress; Quality of life